Biocombustíveis a partir de óleos e gorduras: desafios tecnológicos para viabilizá-los Oils and fats based biofuels: technological chalendges - Paulo A. Z. Suarez (Química Nova, 2009)
Periodically, during petroleum shortage, fatty acids and their derivatives have been used as alternative fuels to those derived from petroleum. Different approaches have been proposed, including the use of neat fats and oils or their derivatives. Indeed, the utilization of biodiesel produced by alcoholysis of triacilglycerides or esterification of fatty acids, or hydrocarbons obtained from cracking of fatty materials were studied and used in several countries. Increasing concerns about energy security and climate changes have lead several countries, including Brazil, to start up biofuels programs. Different technologies are currently being developed in order to produce biofuels with economical feasibility. In this work are discussed alternative fatty raw-materials and processing technologies that are currently being studied in order to produce fuels suitable to sustainable substitute diesel fuel.